ANALYSIS OF EVALUATIVE COMPARISON OF THE FOOD AID PROGRAMS IN SOJOMERTO VILLAGE, GEMUH SUB-DISTRICT, KENDAL DISTRICT - Nurhayati Nurhayati; Slamet Santoso (Journal of Public Policy and Management Review, 2019)
Poverty is significant issue for developing countries especially in Indonesia. One of poverty prevention effort in Indonesia is issuing a policy. In Central Java, especially in Kendal Regency, Kendal Regency Regional Government Number 4 year 2011 Concerning Poverty Prevention in Kendal Regency have been issued. This policy manifested in the Food Aid Programs (Rastra and Non-Cash Food Support / BPNT). BPNT Program exist to substitute Rastra Program. These become primary idea to conduct comparison between Rastra Program with BPNT Program. This research aimed to analyse performance difference in poverty prevention in Sojomerto Villlage of Gemuh Sub-district of Kendal Regency on Rastra and BPNT Pograms. This research used quantitative method with comparative research type. Research result showed performance difference on poverty prevention in Sojomerto Village. Such difference could be viewed from policy evaluation criteria of William N. Dunn specifically effectiveness, efficiency, sufficiency, equity, responsiveness and accuracy. Researcher recommended to government the following for BPNT Program, proposed not to receive anything good from the Rastra program, namely the amount of rice given to KPM. In the Rastra program, Beneficiary Families receive 15 kg of rice. While the BPNT program, rice is given as much as 10 kg and ¼ kg of eggs. The goverment does not reduce the amount of rice given. Thus, the Beneficiary Families will recieve the given rice will be sufficient, given by representing eggs as much us ¼ kg.